2019
DOI: 10.1155/2019/2052675
|View full text |Cite
|
Sign up to set email alerts
|

Mangiferin Improved Palmitate-Induced-Insulin Resistance by Promoting Free Fatty Acid Metabolism in HepG2 and C2C12 Cells via PPARα: Mangiferin Improved Insulin Resistance

Abstract: Elevated free fatty acid (FFA) is a key risk factor for insulin resistance (IR). Our previous studies found that mangiferin could decrease serum FFA levels in obese rats induced by a high-fat diet. Our research was to determine the effects and mechanism of mangiferin on improving IR by regulating FFA metabolism in HepG2 and C2C12 cells. The model was used to quantify PA-induced lipid accumulation in the two cell lines treated with various concentrations of mangiferin simultaneously for 24 h. We found that mang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 32 publications
3
37
0
1
Order By: Relevance
“…IR causes the body to produce compensation and secrete more insulin due to the body's decreased glucose regulation function. This result leads to the hydrolysis of triglycerides in the body and the increase of plasma fatty acid content, which ultimately promotes the increase of blood sugar and is excreted from the kidney [36,37]. At the same time, IR prevents insulin from efficiently inhibiting lipase activity.…”
Section: Discussionmentioning
confidence: 99%
“…IR causes the body to produce compensation and secrete more insulin due to the body's decreased glucose regulation function. This result leads to the hydrolysis of triglycerides in the body and the increase of plasma fatty acid content, which ultimately promotes the increase of blood sugar and is excreted from the kidney [36,37]. At the same time, IR prevents insulin from efficiently inhibiting lipase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy monitoring indicators were considered. Specifically, the level of FBG, FINS, HbA1c, FFA with a close relationship with IR occurrence and promotes the development of IR-type diabetes [ 39 ]) in serum was determined, and the HOMA-IR in each group was conducted. After ART treatment, FBG, FIINS, HbA1C, FFA concentration, and HOMA-IR were decreased compared with those of HFD group mice (Figures 3(b) – 3(f) ).…”
Section: Resultsmentioning
confidence: 99%
“…To further facilitate evidence-based cellular exploration, the IR model of C2C12 cells induced by PA was accustomed. After the ARTC intervention, we found that ARTC treatment promoted PA-induced glucose consumption in a dose-dependent manner [ 39 ]. The intervention of ART reduced the expression of TNF- α and MCP-1 levels in the IR model cells, implying the anti-inflammatory effect of ART.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive FFAs-induced lipids deposition in tissues is one of the most important factors that induce oxidative stress and in ammation in various tissues and organs of the body [25][26][27]. PA is an important member of the saturated fatty acid family and closely involves in the occurrence and development of a lot of diseases in the body, such as insulin resistance and T2DM [28][29][30]. When the body's lipids are overloaded, the lipid balance is disrupted, leading to lipid metabolism system unable to proceed normally and cause lipotoxicity [31,32].…”
Section: Discussionmentioning
confidence: 99%